2005
DOI: 10.1042/bj20041348
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of murine 1-acyl-sn-glycerol 3-phosphate acyltransferases and their regulation by PPARα in murine heart

Abstract: In response to UV irradiation, mammalian cells elicit a gene expression programme designed to repair damage and control cell proliferation and apoptosis. Important members of this stress response include the NF-kappaB (nuclear factor-kappaB) family. However, the mechanisms by which UV irradiation activates NF-kappaB are not well understood. In eukaryotes, a variety of environmental stresses are recognized and remediated by a family of protein kinases that phosphorylate the alpha subunit of eIF2 (eukaryotic ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
92
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(101 citation statements)
references
References 46 publications
8
92
1
Order By: Relevance
“…Previous attempts for its isolation suggested that protein(s) of an apparent molecular mass of 50-60 kDa could be labeled with a photoreactive azido-lysoPC derivative in a partially purified microsomal fraction containing a LPCAT activity (10). To identify candidate LPCATs in RBCs, we searched databases for proteins carrying the E. coli plsC domain, which is characteristic of all known 1-acyl-sn-glycerol-3-phosphate acyltransferases (11)(12)(13), and excluded all known enzymes that have been described as lysophosphatidic acid acyltransferases (LPAATs). We focused particularly on two gene products of unknown function with a predicted molecular mass of 60 kDa, annotated in human as AYTL1 and AYTL2 and as Aytl1 and Aytl2 in mouse (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous attempts for its isolation suggested that protein(s) of an apparent molecular mass of 50-60 kDa could be labeled with a photoreactive azido-lysoPC derivative in a partially purified microsomal fraction containing a LPCAT activity (10). To identify candidate LPCATs in RBCs, we searched databases for proteins carrying the E. coli plsC domain, which is characteristic of all known 1-acyl-sn-glycerol-3-phosphate acyltransferases (11)(12)(13), and excluded all known enzymes that have been described as lysophosphatidic acid acyltransferases (LPAATs). We focused particularly on two gene products of unknown function with a predicted molecular mass of 60 kDa, annotated in human as AYTL1 and AYTL2 and as Aytl1 and Aytl2 in mouse (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Five proteins have been identified in human and mouse containing the so-called plsC domain of the E. coli PlsC protein and have been reported to acylate lysoPA in the presence of acyl-CoA (12,13). However, systematic annotation of any plsC-containing protein homologous to AGPAT as an additional member of this family has led to some confusion, because not all appear to use lysoPA as substrate.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have revealed that liver fatty-acid binding protein can transport 1-acyl glycerol-3-phosphate from the mitochondria to target microsomes [13]. However, whether fatty-acid binding protein serves as a transporter in vivo remains elusive.Based on their known homology to mtGPAT, other acyltransferases for TAG synthesis in the Kennedy pathway were subsequently identified and studied, including AGPAT, DGAT and their isoforms [18,[22][23][24][25][26][27]. To date, eight AGPAT genes have been identified, although the physiological functions of each are not well established [28,29].…”
mentioning
confidence: 99%
“…Structural analysis of several glycerolipid acyltransferases from a variety of organisms has revealed a critical domain responsible for their catalytic activity (12). The critical amino acid motif of H(X) 4 D is present within this domain in all glycerolipid acyltransferases that have been studied to date (8)(9)(10)(11). To our knowledge, the cloning of any lysoPC acyltransferase has not been reported.…”
mentioning
confidence: 99%
“…Only a few glycerol lipid acyltransferases have been cloned and sequenced (7)(8)(9)(10)(11). Structural analysis of several glycerolipid acyltransferases from a variety of organisms has revealed a critical domain responsible for their catalytic activity (12).…”
mentioning
confidence: 99%